2012
DOI: 10.1371/journal.pone.0032543
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Bifidobacteria with Optimised 16S rRNA-Gene Based Pyrosequencing

Abstract: The 16S rRNA gene is conserved across all bacteria and as such is routinely targeted in PCR surveys of bacterial diversity. PCR primer design aims to amplify as many different 16S rRNA gene sequences from as wide a range of organisms as possible, though there are no suitable 100% conserved regions of the gene, leading to bias. In the gastrointestinal tract, bifidobacteria are a key genus, but are often under-represented in 16S rRNA surveys of diversity. We have designed modified, ‘bifidobacteria-optimised’ uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
147
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(152 citation statements)
references
References 44 publications
3
147
0
Order By: Relevance
“…This may be another factor which led to varying results seen among milk, as well as fecal microbiota, and has prompted many researchers to include a bead-beating step to adequately lyse cells. 58 Further studies have also detected identical strains of Lactobacillus, Bifidobacterium, and Staphylococcus in both HM and infant feces, reaffirming HM as a potential source of probiotic and commensal bacteria involved in colonization of the immature infant GI tract. 61,67 Culture-independent methods have detected more than 700 different bacterial species in milk, including obligate anaerobes and butyrate-producers.…”
Section: Human Milk Microbiotamentioning
confidence: 82%
See 1 more Smart Citation
“…This may be another factor which led to varying results seen among milk, as well as fecal microbiota, and has prompted many researchers to include a bead-beating step to adequately lyse cells. 58 Further studies have also detected identical strains of Lactobacillus, Bifidobacterium, and Staphylococcus in both HM and infant feces, reaffirming HM as a potential source of probiotic and commensal bacteria involved in colonization of the immature infant GI tract. 61,67 Culture-independent methods have detected more than 700 different bacterial species in milk, including obligate anaerobes and butyrate-producers.…”
Section: Human Milk Microbiotamentioning
confidence: 82%
“…34,50,51 Conversely, Palmer and colleagues 2 reported very low levels of bifidobacteria in all infants with varied dietary patterns; however, these findings are likely due to the 8F universal primer that was used in the study having a three base pair mismatch against B. longum, and that Bifidobacterium genus in general does not have 100% sequence identity to the 8F primer sequence. 58 Infants harboring similar relative abundances of Bifidobacterium still exhibit some variance in diversity, 34,39,42 and stability 51 of populations at the species level. For example, B. longum and B. breve are the dominant species in BF infants, 27,[41][42][43] whereas FF infants also harbor adultassociated bifidobacterial species, such as B. adolescentis.…”
Section: (Finland)mentioning
confidence: 99%
“…In addition, 5.5 ± 4% of sequences were not assigned to any bacterial phylum. It should be noted that while our study was underway the sequencing primers used for 16S rRNA amplicon sequencing were reported to underrepresent the phylum Actinobacteria and specifically Bifidobacterium species (8).…”
Section: Experimental Design and Chemical Composition Of Gos/rp-g28mentioning
confidence: 95%
“…The extracted DNA was used to generate an amplicon based library using Bifidobacterium optimised PCR primers 357F/926Rb (357F -CCTACGGGAGGCAGCAG, 926Rb -CCGTCAATTYMTTTRAGT, the base that differs from the standard 926R primer is bolded) that target the V3-V5 hypervariable regions of the 16S rRNA gene as described by Sim et al [21]. Each sample was barcoded with a Multiplex Identification (MID) tag (10 bp in length).…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%